-20-9b+1=16b+20

Simple and best practice solution for -20-9b+1=16b+20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -20-9b+1=16b+20 equation:


Simplifying
-20 + -9b + 1 = 16b + 20

Reorder the terms:
-20 + 1 + -9b = 16b + 20

Combine like terms: -20 + 1 = -19
-19 + -9b = 16b + 20

Reorder the terms:
-19 + -9b = 20 + 16b

Solving
-19 + -9b = 20 + 16b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-16b' to each side of the equation.
-19 + -9b + -16b = 20 + 16b + -16b

Combine like terms: -9b + -16b = -25b
-19 + -25b = 20 + 16b + -16b

Combine like terms: 16b + -16b = 0
-19 + -25b = 20 + 0
-19 + -25b = 20

Add '19' to each side of the equation.
-19 + 19 + -25b = 20 + 19

Combine like terms: -19 + 19 = 0
0 + -25b = 20 + 19
-25b = 20 + 19

Combine like terms: 20 + 19 = 39
-25b = 39

Divide each side by '-25'.
b = -1.56

Simplifying
b = -1.56

See similar equations:

| 2(6x+5)=3x-26 | | 3-19p=-18p+20 | | -6w-12+2w=28 | | (10/3)/(2/21) | | -4/-5y=72 | | -3m=-6-5m | | 52/650 | | (1/4x-6)=(2/3x+3) | | 4u=3u-8 | | 2[3x-(4x-8)]=5(x-8) | | 3x+15=11+5x | | -7x+16=8(5x+2) | | -8p=176 | | 4(x+2)/6 | | 3+5(-8a-1)=-6-(3a-4) | | 0.15-0.01(x+1)=-0.03(2-x) | | (-2x/11)=66 | | 7x+3=2(3x+1)-x+8 | | x+6=15-x | | 13/6+x=6 | | 16n^2-8n-15=0 | | 2x-5y=4x+15 | | 5/2x=3/2x-4 | | 35x^4-2x^2-1=0 | | 14w-18=94 | | 9(x+6)+5=59 | | -533-(-276)= | | -2(-6k-5)=-15+7k | | -x+3+11x=-3+4x+48 | | .5x+.05x=256 | | 4(5k-5)+19=-9+2(3k-8) | | 13+3(2x-5)=1-2(3-6x) |

Equations solver categories